Understanding the Rise and Fall of Rural Specialty Agriculture from Social–Ecological Land System Perspective: A Longitudinal Case Study in China - Xue Wang; Mingyu Wang; Lianbing Gong; Chuangchuang Yu (Land)
Specialty agriculture, promoted in China to enhance rural revitalization and farmers’ wellbeing, depends heavily on local social–ecological conditions and land transformations. However, existing studies often emphasize socio-institutional successes while oversimplifying ecological complexity and neglecting failures. This study examines the rise and fall of rural specialty agriculture through a social–ecological land system perspective, using the cherry tomato industry in C Town, China, as a case study. Drawing on qualitative data from field investigations and interviews, we adapt an extended Social–Ecological Systems Framework (SESF) to analyze interactions among governance subsystems, land resources, and external shocks, and their role in social–ecological transitions. Our findings show that the shift from farmer-led self-organization to government-driven and enterprise-dominated governance significantly undermined system resilience and adaptability. Although external interventions initially spurred industrialization and scaling, they marginalized farmers, leading to the system’s collapse under stressors like market fluctuations and environmental challenges. Our findings highlight the importance of inclusive governance for sustaining land-based agricultural systems, and point to the need of prioritizing farmer autonomy, sustainable land use planning, and adaptive governance to ensure the resilience and long-term sustainability of specialty agriculture systems.